Medusa’s head: Boss rattlers, rattlesnake queens, and goddamn true love in Harry Crews’s "A Feast of Snakes" - Hanssen, Ken R. (Adam Mickiewicz University, 2016)
After his death in 2012, there has been a notable resurgence of both popular and critical interest in the fiction of American writer Harry Crews. Frequently discussed in the context of Southern gothic, Crews’s novels are notable for their grim and darkly funny tales of life among the rural poor in the worst hookworm and rickets part of Georgia, USA. Still, while the regional identity of Crews’s fiction is strong, his subtle and deeply sympathetic creative imagination tackles questions of universal significance. In the novel A Feast of Snakes (1976), Crews’s finest and most multi-layered work, we are introduced to former high-school football quarterback Joe Lon Mackey on the eve of Mystic, Georgia’s annual Rattlesnake Roundup. Through his sensitive and deeply-felt portrayal of Joe Lon’s failed struggle to reconcile with the traumas of the past and establish meaning and a sense of purpose in life, a development culminating in the liquidation of a snake-handling preacher, a sheriff’s deputy, his own high-school sweetheart, and a random bystander, Crews not only explores the deterministic cultural and socio-economic attributes of the rural south, but also gives articulation to a reflective consciousness far more individuated and multifaceted than allowed for in recent critical discourse. This sombre ending is perhaps what Todorov would term “the realization of an order always preordained,” but it would be a mistake to dismiss it as merely the inevitable outcome of yet another southern boy’s unarticulated rage against modernity. Struggling endlessly like the pitfighting dogs his daddy breeds, Joe Lon, entangled in the determinants of his existence, comes to give mimetic shape to a contemporary American identity both utterly strange and jarringly familiar.
Keywords: Harry Crews; Southern fiction; gothic; trauma; mimesis; naturalism; determinism; psychological realism